Analisis IPA Dan CSI Terhadap Kepuasan Pelanggan Market Place Pada Pelayanan J&T Express Indonesia - Ulta Rastryana; Usran Masahere; Santi Rusmayanti (FEB Universitas Sultan Ageng Tirtayasa, 2022)
Currently, with the advancement of information technology and the increasing number of Indonesian markets, more than 60% of Indonesians including millennials, entrepreneurs, employees, and housewives, have switched to using marketplaces such as Tokopedia, Shopee, Lazada, etc. for their daily needs. In this study, researchers want to summarize customer satisfaction when using the Shopee marketplace, especially those related to the services provided by PT. J&T Express Indonesia is located at the Koja Jakarta Utara. Researchers used raw data from a questionnaire of 100 respondents and used the IPA and CSI methods as analytical measuring tools to understand customer satisfaction. From the results of this study using the IPA method, there are several indicators of customer satisfaction that need to be improved both in quadrants I, II, III, and IV. Of the four quadrants, quadrant IV needs to improve the performance of the J&T Express company, although customers are satisfied customers also don't expect much from the J&T Express company. And if use the CSI method, you get 80.36%, which means that customers are satisfied with the services provided by J&T Express Indonesia.